Utilização das equações diferenciais para modelagem de sistemas de engenharia da UFERSA Campus Caraúbas - Alves, Thâmara Dayane Batista (Universidade Federal Rural do Semi-Árido, 2018)
Differential equations are equations whose unknown is a function that appears in the equation in the form of their derivatives, used in the construction of mathematical models of physical phenomena, so your study is an extensive field of pure mathematics and applied. The modeling of many real-world problems using ordinary differential equations (ODE), is an important tool that has great potential and can describe many phenomenons. In this way, this work aims to present and study mathematical models described by differential equations present in the area of engineering. The chosen were civil, electrical engineering and mechanics for being the second-cycle courses offered by Universidade Federal Rural do Semi-Árido campus Caraúbas. The phenomena were modeled beam deflection, cooling of ceramic blocks, electric RC circuits and LRC, mechanical, automotive suspensions and safety valves and pressure relief. The modeling of the method.
Monografia
Keywords: Modelagem; Equações diferenciais; Engenharia; Aplicações; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA